Health and Economic Growth Nexus: Evidence from Selected Sub-Saharan African (SSA) Countries - Sarpong, B.; Nketiah-Amponsah, E.; Owoo, N.S. (Global Business Review, 2018)
This article examines the effect of health on long-run economic growth in 35 selected sub-Saharan African (SSA) countries using panel data covering the period 1997–2016. Data were analysed using panel co-integration tests, panel Granger causality tests and the dynamic OLS estimator. The results show that health human capital is a significant determinant of long-run economic growth in SSA. In particular, a percentage increase in health human capital proxied by per capita health expenditure increases growth by 0.207 per cent. The prime contribution of this article to the literature lies in the results of the novel interaction between health human capital and institutional quality. More precisely, by using the dynamic panel least square estimation technique, we found that the effect of institutional quality on economic growth is positive and robust only when it is interacted with the required health human capital. It is further revealed that the causal link between economic growth and health is bidirectional.
Keywords: Economic growth; Health human capital; Sub-Saharan Africa; Panel dynamic OLS; Panel co-integration; Panel causality